Zeolites as supports for the biorecovery of hexavalent and trivalent chromium - Silva, Bruna Andreia Nogueira Airosa (2008)
The aim of this study is the preparation and characterization of new catalytic materials to be used in oxidation reactions through the recovery of heavy metals in wastewater. The recovery of Cr(III) and Cr(VI) from aqueous solutions by an Arthrobacter viscosus biofilm supported on NaY zeolite was investigated. Experiments were repeated without the bacteria for comparison purposes. The batch method has been employed, using solutions with chromium concentrations of 10 mg L-1, 25mgL-1, 50mgL-1 and 100 mg L-1. Cr(III) was easily removed from solution due to its positive charge which allows the entrapment in the framework zeolite by ion exchange. However, due to its anionic form Cr(VI) was only removed in the presence of the biofilm that performs its reduction to Cr(III), followed by ion exchange in the zeolite. The best uptake was achieved for initial concentration of 100 mg L-1: 14mg g-1 zeolite for Cr(III) by both systems and 3 mg g-1 zeolite for Cr(VI) by the zeolite with the bacterium biofilm. The modified zeolite samples have been fully characterized by surface analysis (XRD, XPS), chemical analyses (ICPAES), spectroscopic method (FTIR) and microscopic analysis (SEM). The results show that the biofilm of A. viscosus supported on NaY zeolite is able to recover chromium from dilute solutions and the framework zeolite remains unchanged after chromium biosorption.